Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area

A high resolution record of the last deglaciation in the southern Tyrrhenian Sea: environmental and climatic evolution - Buccheri, G.; Capretto, G.; Di Donato, V.; Esposito, P.; Ferruzza, G.; Pescatore, T.; Russo Ermolli, E.; Senatore, M. R.; Sprovieri, M.; Bertoldo, M.; Carella, D.; Madonia, G. (Marine Geology, 2002)
A multidisciplinary study was carried out on core C106 collected in the Salerno Gulf (southern Tyrrhenian Sea). Two tephra layers recovered in the core, δ18O record of Globigerinoides ruber and Globigerina bulloides and seven 14C calibrated ages provided the stratigraphic framework. The core sediments cover the last 28 kyr BP. Seismo-stratigraphic analysis of a high resolution acoustic profile, integrated by the dated core samples, allowed us to reconstruct the architecture and age of sedimentary bodies on the continental shelf. An integrated study based on different taxonomic groups (nannofossils, pteropods, foraminifera, and palynomorphs) provided palaeoclimatic trends, in agreement with changes in the isotopic composition of oxygen. The upper part of the Last Glacial period, the deglaciation phase and the Holocene were identified. Correlation between marine and continental records of palaeoenvironmental changes confirms a similar reconstruction of the last deglaciation as in the central and southern Mediterranean Sea. The Late Pleistocene–Holocene boundary was recognised at about 11.7 kyr BP. Between about 9.5 and 6 kyr BP and at 3.3 kyr BP some warmer episodes were recorded. The measured lower isotopic values, together with some features of the fossil assemblages recorded from 9.5 to 6 kyr BP, may be related to the oceanographic setting that led to the deposition of Sapropel S1 in the Mediterranean basin.
Keywords: isotopes; late quaternary; palaeoclimatology; sedimentology; seismic stratigraphy; Tyrrhenian Sea